El Contraalmirante Aníbal Olivieri : ¿Ministro de Marina de la Nación o “Ministro de Perón”? - Santiago, María Eugenia (2019)
Fil: Santiago, María Eugenia. Pontificia Universidad Católica Argentina; Argentina